Implementation Of Legal Protection Of Children And Women As Victims Of Sexual Crimes - Weldon Manurung; Junifer Dame Panjaitan (International Journal of Social Research, 2023)
This research explores the multifaceted nature of sexuality, emphasizing its significance in human survival and development within the context of Indonesian society. The study delves into the negative aspects associated with sexuality, particularly sexual abuse, which manifests in various forms such as harassment, exploitation, and violence. Alarming levels of sexual abuse among adolescents are highlighted, with contributing factors ranging from the circulation of pornographic content to a lack of understanding of religious values and inadequate sex education. The patriarchal domination theory is introduced to underscore the unequal power dynamics that contribute to crimes against women and children. The empirical juridical method is employed to examine the legal protection afforded to children and women in the face of sexual crimes, encompassing both preventive and repressive measures. The Child Protection Law and related regulations serve as the legal framework for this protection. The research identifies factors influencing sexual crimes, including internal factors such as psychological and mental states, external factors like economic conditions and societal influences, and the role of victims. The study concludes by emphasizing the importance of legal education and appropriate sanctions to address and prevent sexual crimes in the future.